A new method to estimate slab dip direction using receiver functions and its application in revealing slab geometry and a diffuse plate boundary beneath Sumatra - Feng, Mingye (2023)
While dip direction is a fundamental parameter of slab geometry, it is rarely estimated quantitatively. Here, we develop a new method, Dip Direction Searching (DDS), of receiver functions (RFs) that reduces the uncertainty of slab dip direction estimation from tens to several degrees. DDS can also resolve the thickness and depth of a dipping structure. We then apply DDS to the RFs in the Sumatran subduction zone. Travel time differences of the converted phases from the upper and lower (oceanic Moho) boundaries of the dipping low-velocity layer (LVL) along the plate interface show a thickness of 10–14 km. The results also show increased dip direction of the slab Moho from 47 ± 5.3° in southern Sumatra to 70 ± 10.7° in northern Sumatra, indicating a complicated slab geometry and internal deformation along strike. Similar dip directions are obtained for the upper and lower LVL boundaries beneath Nias and Enggano forearc islands in the north and south, whereas we find a larger discrepancy of ∼14–23° beneath Siberut and Pagai in between. The thicker LVL with a non-negligible difference in the dip directions of its upper and lower bounds in the center of Sumatra is interpreted as a partially serpentinized mantle layer above the oceanic crust, forming a distinct channel atop the subducting slab. Our results provide basic observational constraints on the structure and geometry of the oceanic slab and associated subduction processes. Both synthetics and data analyses also indicate DDS can be applied in other subduction zones and for other dipping interfaces.